2011
DOI: 10.1111/j.1365-2249.2011.04483.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil treatment attenuates lung and kidney injury due to overproduction of oxidant activity in a rat model of sepsis: a biochemical and histopathological study

Abstract: SummarySepsis is a systemic inflammatory response to infection and a major cause of morbidity and mortality. Sildenafil (SLD) is a selective and potent inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase PDE5. We aimed to investigate the protective effects of sildenafil on caecal ligation and puncture (CLP)-induced sepsis in rats. Four groups of rats were used, each composed of 10 rats: (i) 10 mg/kg SLD-treated CLP group; (ii) 20 mg/kg SLD-treated CLP group; (iii) CLP group; and (iv) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 64 publications
5
45
1
1
Order By: Relevance
“…The beneficial effects of propofol administration on the inflammation of lungs after intravenous endotoxin administration has been shown in rats [42][43][44][45][46][47][48][49][50].…”
Section: New Approachesmentioning
confidence: 99%
“…The beneficial effects of propofol administration on the inflammation of lungs after intravenous endotoxin administration has been shown in rats [42][43][44][45][46][47][48][49][50].…”
Section: New Approachesmentioning
confidence: 99%
“…Cadirci et al [32] reported effects of sildenafil (10 and 20 mg/ kg/p.o.) in remote organs, including the lung and kidneys, in a rat model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Moreover, the beneficial effects of sildenafil have been shown in the balance of oxidation and antioxidation via decreasing oxidative and nitrosative stress in inflammatory events. [9,23,[30][31][32][33][34] However, there is no study in the literature focusing on the effects of sildenafil in remote organ injury induced by severe burn except our previous study focusing on acute lung injury. [9] The purpose of the present study was to evaluate the effects of different dosages of sildenafil in distant organs, such as liver and kidneys, due to severe scald burn injury in rats.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Restoration of oxygen levels upon reperfusion causes a surge in the generation of reactive oxygen species and pro-inflammatory mediators and cells to exacerbate ischemic injury [33]. PDE5 inhibitors have been reported to increase antioxidant defenses and decrease inflammation [34] and apoptosis [35]. Indeed, these agents were shown to decrease I/R injury in renal tissue [35,36].…”
Section: Ischemia Reperfusion Injurymentioning
confidence: 99%